Biocomposite Polyvinyl Alcohol/Ferritin Hydrogels with Enhanced Stretchability and Conductivity for Flexible Strain Sensors - Qiang Fu; Junxiao Tang; Weimin Wang; Rongjie Wang (Gels)
Protein-based hydrogels with stretchability and conductivity have potential applications in wearable electronic devices. However, the development of protein-based biocomposite hydrogels is still limited. In this work, we used natural ferritin to develop a PVA/ferritin biocomposite hydrogel by a repetitive freeze–thaw method. In this biocomposite hydrogel, ferritin, as a nano spring, forms a hydrogen bond with the PVA networks, which reduces the crystallinity of PVA and significantly improves the stretchability of the hydrogel. The fracture strain of the PVA/ferritin hydrogel is 203%, and the fracture stress is 112.2 kPa. The fracture toughness of the PVA/ferritin hydrogel is significantly enhanced to 147.03 kJ/m3, more than 3 times that of the PVA hydrogel (39.17 kJ/m3). In addition, the free residues and iron ions of ferritin endow the biocomposite hydrogel with enhanced ionic conductivity (0.15 S/m). The strain sensor constructed from this hydrogel shows good sensitivity (gauge factor = 1.7 at 150% strain), accurate real-time resistance response, and good long cyclic working stability when used for joint motion monitoring. The results indicate that a PVA/ferritin biocomposite hydrogel prepared by a facile method has enhanced stretchability and conductivity for flexible strain sensors. This work develops a new method for the preparation of protein-based hydrogels for wearable electronic devices.